Inter- and intra-observer reproducibility of quantitative renographic parameters of differential function and renal drainage in children. (August 2013) - Tondeur, Marianne; Nogarède, Cécile; Donoso, Gilda; Piepsz, Amy
Abstract Purpose. To evaluate inter- and intra-observer reproducibility of renographic quantitative parameters of input and output in children. Methods. 100 children with unilateral or bilateral uropathy were selected, aiming to cover the entire range of ages, overall glomerular filtration rate (GFR), differential renal function (DRF) and quality of drainage. Renograms were acquired and processed according to the EANM guidelines, using a non-commercial software. Following parameters were tested: DRF using integral and Patlak methods, normalized residual activity (NORA) and output efficiency (OE) at 20 min and on the late post-erect post-micturition acquisition. Three observers from the same department and one from Santiago (Chile) processed independently the 100 renograms using the same renal software. Two observers reprocessed the 100 renograms again two months later in order to evaluate the intra-observer reproducibility. Results and conclusion. No significant difference was observed between the four observers, whatever the considered parameter of input function or output. For left DRF (Integral and Patlak methods), 95% of the individual differences were between −5% and +5 %. They were between −0.5 and +0.5 units for both NORA 20 and NORA PM, and between −10% and +10% for OE 20 and OE PM. Inter-and intra- observer reproducibility were comparable. Outliers tended to be more frequent for Patlak than for Integral. Very low GFR (< 20 mL/min/1.73 m2), very young age (first days of life), huge megaureters, NORA values higher than 2.0, OE values below 60% and bladder in the renal background area (ectopic kidney) were the main characteristics of extreme differences.